PEMBERDAYAN EKONOMI PETANI LELE DALAM MENUJU IKON DESA LELE (KASUS DESA SENGGOWAR, KEC. GONDANG) KABUPATEN NGANJUK - Nugroho, Sigit Dwi; -, Purwadi; sulistyowati, lisa (Jurnal Bisnis Indonesia, 2020)
Abstract Senggowar Village is a part of Gondang sub-district, Nganjuk district, a village that wishes to become a village with a “catfish” icon. Economic problems cause many parents to work outside the home, so that their children are less attention and get along with the environment that is not true. Some people work in agriculture as agricultural laborers, especially primary products with inadequate income. Village officials and community leaders look for solutions in various opportunities by introducing villages with the icon "Lele Village". Because Catfish is now an animal necessity at a price that is quite affordable by the wider community. The Village Government formed 2 Farmer Groups namely: Mina Tirta 1 and Mina Tirta 2. The activities of these farmer groups are still limited to exhibition activities held by the Nganjuk District Government related to village potential. Sustainability activities have not been carried out optimally, due to the limited knowledge and technology of the community about catfish cultivation and diversification of food made from raw catfish. For this reason, a program of activities for the "Lele Village" was considered. The solution offered by making artificial ponds with tarpaulins that can be done in a narrow yard. Post-harvest handling of processed products from catfish include: Abon Catfish, Catfish Meatballs, Catfish Chips, Catfish Flour, Catfish Dumplings. Marketing with an online model, accounting books, and empowerment of farmer group cooperatives. Keywords: Empowerment, tarpaulin ponds, catfish   Abstrak Desa Senggowar adalah bagian dari kecamatan Gondang, kabupeten Nganjuk, merupakan desa yang berkeinginan menjadi desa berikon “lele”.  Permasalahan ekonomi mengakibatkan banyak orang tua bekerja di luar rumah, sehingga  anak anaknya  kurang diperhatikan  dan bergaul dengan lingkungan yang kurang benar. Sebagian masyarakat  bekerja pun dibidang pertanian sebagai buruh tani khususnya produk primer dengan pengahasilan yang kurang memadai. Perangkat desa dan  tokoh masyarakat mencari solusi diberbagai kesempatan dengan mengenalkan desa ber ikon “Desa Lele”. Karena Lele sekarang menjadi kebutuhan hewani dengan harga yang cukup terjangkau oleh masyarakat secara luas. Pemerintah Desa membentuk 2 Kelompok Tani yaitu : Kelompok Mina Tirta 1 Mina Tirta 2 Senggowar. Kegiatan kelompok tani ini masih terbatas pada kegiatan pameran yang diadakan Pemerintah Kabupaten Nganjuk terkait potensi desa. Keberlanjutan kegiatan belum dilakukan secara optimal, karena keterbatasan pengetahuan dan teknologi masyarakat tentang budidaya lele dan diversifikasi pangan berbahan baku dari Lele.  Untuk itu dipikirkan program kegiatan menuju “Desa Lele”. Solusi yang ditawarkan dengan pembuatan kolam buatan dengan terpal yang bisa lakukan di pekarangan yang sempit. Penanganan pasca panen produk olahan dari lele diantaranya : Abon Lele,Bakso Lele, Kripik Lele, Tepung Lele, siomay lele.  Pemasaran dengan model on line, pembukuan akuntansi, serta pemberdayaan koperasi kelompok tani. Kata Kunci : Pemberdayaan, kolam terpal, lele